Effect of surface topography on anisotropic friction of graphene layers. (October 2020) - Ding, Mingda; Cong, Yu; Li, Ruiyang; Xu, Fan
Abstract: Tribological behavior of graphene layers has been a focus of intensive research interest since its crystal lattice structure can be exploited to achieve incommensurate contact, leading to nearly zero friction, namely structural superlubricity. However, wrinkling undulations are omnipresent on graphene and difficult to be completely eliminated, which inevitably resists superlubricity in reality. Here, we explore how the presence of surface wrinkles affects nanotribological behavior of graphene sliding systems. Using a dimensionless parameter based on the topographic geometry, we propose a set of quantitative criteria permitting incommensurate-induced low friction even superlubricity to retain, despite the presence of surface wrinkles. Failing the criteria, achievement of superlubricity on wrinkled surface becomes implausible with unfavorable anisotropy and considerable friction. Besides, we examine the influence of diverse spatial topographic patterns such as stripe, checkerboard and herringbone on tribological behavior, and reveal that surface wrinkles can precisely tune the oscillating undulation of friction response. The proposed criteria may serve as an indicative reference that allows predicting the state of friction on practical, wrinkled graphene, and eventually assist the design of nanotribological systems with tunable friction.